In Situ Control of Separate Electronic Phases on SrTiO3 Surfaces by Oxygen Dosing. Issue 34 (22nd June 2016) - Dudy, Lenart; Sing, Michael; Scheiderer, Philipp; Denlinger, Jonathan D.; Schütz, Philipp; Gabel, Judith; Buchwald, Mathias; Schlueter, Christoph; Lee, Tien‐Lin; Claessen, Ralph
Abstract : Insulating SrTiO3 (STO) can host 2D electron systems (2DESs) on its surfaces, caused by oxygen defects. This study shows that the STO surface exhibits phase separation once the 2DES is formed and relates this inhomogeneity to recently reported magnetic order at STO surfaces and interfaces. The results open pathways to exploit oxygen defects for engineering the electronic and magnetic properties of oxides.